Market access - Perini, Sofía C.; Tejeda Rodríguez, Agustín; Morales Opazo, Cristian; Weber, Regine; Miranda, Silvia Helena Galvao de (Instituto Interamericano de Cooperación para la Agricultura, 2021)
Market Access is one of the most significant and challenging pillars in the WTO Agreement on Agriculture due to its magnitude and the impacts associated with a change in agricultural trade rules. Increasing Market Access continues to be a relevant topic for Latin America and the Caribbean (LAC), a region which encompasses the world’s largest agri-food exporters as well as net-agri-food importing countries. While LAC produce about a seventh of global exports in agri-food products63, food and nutrition security remains a concern in several of its countries, with 14% of the population classifying as severely food insecure, 41% as moderately or severely food insecure and 49.8 million people being undernourished in 2020 (FAO, IFAD, UNICEF, WFP and WHO, 2021). Negotiations on market access are key for both LAC net agrifood exporting and importing countries with the objective to grant access to the products of exporters and to ensure the supply and food security not only for LAC importers but at global scale.